2017
DOI: 10.1007/s13205-017-0719-4
|View full text |Cite
|
Sign up to set email alerts
|

Fungal pretreatment of sweet sorghum bagasse with supplements: improvement in lignin degradation, selectivity and enzymatic saccharification

Abstract: Sweet sorghum bagasse (SSB) from food processing and agricultural industry has attracted the attention for uses in production of biofuel, enzymes and other products. The alteration in lignocellulolytic enzymes by use of supplements in fungal pretreatment of SSB to achieve higher lignin degradation, selectivity value and enzymatic hydrolysis to fermentable sugar was studied. Fungal strain Coriolus versicolor was selected for pretreatment due to high ligninolytic and low cellulolytic enzyme production resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…An obstacle to the utilization of lignocellulosic waste is the stubbornness of lignin, in which cellulose fibrils are embedded, prevent the conversion of structural polysaccharides into fermentable sugars [109]. In recent reports, physical and chemical pretreatments have been reported to degrade lignin into lignocellulosic biomass within a short time (10-40 min) [110,111].…”
Section: Lignin Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…An obstacle to the utilization of lignocellulosic waste is the stubbornness of lignin, in which cellulose fibrils are embedded, prevent the conversion of structural polysaccharides into fermentable sugars [109]. In recent reports, physical and chemical pretreatments have been reported to degrade lignin into lignocellulosic biomass within a short time (10-40 min) [110,111].…”
Section: Lignin Degradationmentioning
confidence: 99%
“…It was reported that Fe 2+ had a stimulating effect on the lignin degradation of wheat straw by Trametes gibbosa and kept the cellulose degradation rate low when the Fe 2+ concentration was 0.5 mM, providing better selectivity in lignin degradation [119]. To achieve a high lignin breakdown and low cellulolytic enzyme production, the fungal strain C. versicolor was selected for biological pretreatment of sweet sorghum bagasse, resulting in excellent cellulose recovery [109]. The biological pretreatment of lignocellulosic biomass by SSF is selective, energy-saving, and effective under mild environmental conditions [114].…”
Section: Lignin Degradationmentioning
confidence: 99%
“…Likewise, fungal treatments in which fungi and actinomycetes directly colonize with the residues or enzymatic treatments using lignolytic enzymes help improving biodelignification process (Ilyin et al 2004;Moreno et al 2015). It further needs exposure of suitable mesophilic and thermophilic conditions that may include combined organic and inorganic complexes like CuSO 4 -gallic acid supplement for aggravating high functional bioconversion activities (Mishra and Jana 2017). The bioconversion process can be fastened with the use of such functionally characterized microbial inoculants that possess high enzymatic activities for lignocellulosic degradation (Choudhary et al 2016).…”
Section: Breakdown Of Cellulose and Hemicellulosesmentioning
confidence: 99%
“…Reducing sugar in biomass and its consumption in fermentation was measured using glucose as standard by HPLC (Agilent 1200 series, MN, USA), equipped with refractive index detector (RID) and Hi-Plex H column (300 × 7.7 mm, PL1170-6830, Agilent) maintained at 55 °C and 80 °C, respectively. HPLC grade water was used as the mobile phase eluting at 0.6 mL min −1 (Mishra et al 2017). Consumption of insoluble nutrients was measured by loss of dry weight of biomass in fermentation.…”
Section: Estimation Of Reducing Sugar Insoluble Nutrients' Consumptimentioning
confidence: 99%